Research and Achievement of Redundancy Elimination of Backbone Network - Baojian Liu; Jie Huang; Baosheng Wang; Xiaoxiao Zhang (Dianxin kexue)
Nowadays, WAN transmission process has a lot of duplicate data, these duplicate data make bandwidth of WAN to be serious wasted. In order to solve this problem, a redundant data elimination strategy based on application layer protocol identification（PI-RE）was put forward. Using the combination of data caching and the application layer protocol identification technology, the redundant data of WAN during transmission were found out, so that the same data transferred only once in WAN as much as possible, to reduce the redundant data transmission excessive waste of WAN bandwidth.